2007
DOI: 10.1002/cncr.22918
|View full text |Cite
|
Sign up to set email alerts
|

Low‐molecular weight forms of cyclin E differentiate ovarian carcinoma from cells of mesothelial origin and are associated with poor survival in ovarian carcinoma

Abstract: BACKGROUND. The authors recently reported on the role of cyclin E in differentiating ovarian/primary peritoneal carcinoma from malignant peritoneal mesothelioma using gene expression arrays. In the current study, they analyzed the expression of low‐molecular weight (LMW) forms of cyclin E in ovarian carcinoma, malignant mesothelioma, and benign reactive effusions. METHODS. Cyclin E protein expression was analyzed in 98 effusions (72 ovarian carcinomas, 14 malignant mesotheliomas, and 12 reactive specimens) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 32 publications
0
46
1
Order By: Relevance
“…13e16 The significance of LMW-E, which was originally discovered in breast cancer by our group and subsequently by others, 17e20 has recently been the subject of several review articles. 21e23 These isoforms are also found in ovarian cancer, 4,24 melanomas, 2 gastric cancer, 25 colorectal cancer, 26e28 lung cancer, 29 and renal cell carcinomas 30 and are strongly associated with poor survival in patients. 4,26,31 Work from our laboratory has implicated LMW-E in breast cancer oncogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13e16 The significance of LMW-E, which was originally discovered in breast cancer by our group and subsequently by others, 17e20 has recently been the subject of several review articles. 21e23 These isoforms are also found in ovarian cancer, 4,24 melanomas, 2 gastric cancer, 25 colorectal cancer, 26e28 lung cancer, 29 and renal cell carcinomas 30 and are strongly associated with poor survival in patients. 4,26,31 Work from our laboratory has implicated LMW-E in breast cancer oncogenesis.…”
mentioning
confidence: 99%
“…21e23 These isoforms are also found in ovarian cancer, 4,24 melanomas, 2 gastric cancer, 25 colorectal cancer, 26e28 lung cancer, 29 and renal cell carcinomas 30 and are strongly associated with poor survival in patients. 4,26,31 Work from our laboratory has implicated LMW-E in breast cancer oncogenesis. For example, LMW-E i) is biochemically hyperactive because of its increased affinity for cdk2 and resistance to inhibition by the CDK inhibitors p21 and p27 32 ; ii) is resistant to the growth-inhibiting effects of antiestrogens 33 and aromatase inhibitors 34 ; iii) promotes deregulation of cell cycle, 35 centrosome amplification, 13 and genomic instability 33 ; iv) causes premature inactivation of Cdc25C and PLK1, leading to faster mitotic exit 16 ; v) is sufficient to render human mammary epithelial cells tumorigenic and leads to altered acinar morphogenesis 36 ; vi) phosphorylates Hbo1 to mediate a cancer stem cell-like environment 14 ; and vii) is a downstream oncogenic target of protein kinase Ci.…”
mentioning
confidence: 99%
“…However, in addition to the full length cyclin E, a series of low-molecular-weight isoforms (LMW-Es) is uniquely present in some cancers such as breast, colon, ovarian and hematological malignancies (Scuderi et al, 1996;Wang et al, 1996;Harwell et al, 2000;Davidson et al, 2007). Having the mass from 45 to 33kDa, these LMW forms are generated in a tumor-specific post translational cleavage which is distinct from proteasome mediated degradation of cyclinE.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, metastatic carcinomas to the lung should always be considered when psammoma bodies are microscopically observed. In our case immunochemistry and radiographic scanning helped us establish the diagnosis of papillary lung adenocarcinoma with psammoma bodies.…”
Section: Poster Presentationsmentioning
confidence: 99%
“…Our group previously applied gene expression array technology to the diagnosis of malignant effusions, identifying novel markers differentiating between serous ovarian/peritoneal carcinoma (OC/PPC) and malignant mesothelioma (MM) [1], between serous OC/PPC and breast carcinoma (BC) [2], and between breast and lung adenocarcinoma [3]. Validation of the two first studies in follow-up studies using IHC, flow cytometry (FCM) and quantitative PCR (qPCR) identified several promising markers differentiating these tumors at the mRNA and protein level, including the FOLR1, FOLR3, RAB25, PRAME, EHF and SCARA3 mRNA as markers of OC/PPC, TNXB as MM marker and AZGP1 and SPDEF mRNA as markers of breast carcinoma, as well as claudins, MUC4, Tenascin-X and Folate receptor-α (FRα) as discriminators at the protein level [4][5][6][7][8][9][10][11][12][13][14][15]. Study by another group recently showed good performance of the Tissue of Origin Test array, performed on mRNA from cell blocks, in diagnosing the origin of tumors detected in effusions [16].…”
mentioning
confidence: 99%